Impacto del dictamen de auditoría en el comportamiento del mercado accionario - Arenas Torres, Felipe (2025)
This research aims at analyzing the impact of the external financial audit opinion on the stock market behavior of the main stock market indexes in Argentina, Chile, Colombia and Peru. The research is based on previous studies, such as those by Gutiérrez Barrera (2018), Gutiérrez et al. (2020), and Ccanto (2021), which examine specific markets from a sectoral perspective, highlighting the need to move toward comparative analyses across different markets and stock indices. A descriptive correlational approach was used with event study method based on 408 audit reports issued between 2019 and 2023, representing 87,74 % of the target population. The results evidenced that all the opinions were unqualified and no significant effect was observed on the stock return. Despite the type of opinion, no positive impact was observed on stock value, considering ten days following the opinion disclosure. It is therefore concluded that the audit opinion does not represent a significant impact on the stock market behavior for the analyzed indexes. It is suggested that future research include companies with lower market capitalization and mixed methodological approaches in order to explore different actors’ perception of the auditor’s role of raising trustworthiness on the reasonable nature of financial statements.